Upaya Peningkatan Kapasitas Remaja Menjadi Mental Health Leader pada Kelompok Sebaya Berbasis Spiritual dan Budaya di Panti Asuhan - Lestari, Retno; Hidayah, Ridhoyanti; Sunarto, Muhammad; Nanlohy, Kesya Laura; Zakiya, Fifi Afifatus (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2023)
Adolescents undergo a phase of complex developmental transitions, where this has an impact on increasing vulnerability to emotional and behavioral problems. However, the high prevalence of mental health problems in adolescents is not accompanied by high behavior seeking help regarding adolescent mental health literacy. Orphanages are considered as places that are able to assist and guide the development of adolescents physically, mentally, emotionally, socially, spiritually and culturally. Activities to strengthen emotional mental health provide scientific input in psychiatric nursing courses to strengthen mental nursing interventions in adolescents so that they have optimal psychosocial health development. This activity aims to improve the function of peer groups living in orphanages in influencing adolescent mental health. The form of activities carried out is in the form of socializing the roles and functions of peer groups regarding mental health, stress management and adolescent conflict management. It can be concluded from the results of this activity that the role of mental health leaders who are in orphanages plays an important role in strengthening emotional mental health in peer groups.